2012
DOI: 10.1016/j.ijscr.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Venous bullet embolism and subsequent endovascular retrieval – A case report and review of the literature

Abstract: Venous bullet emboli should be removed endovascularly whenever technically possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 8 publications
3
52
0
Order By: Relevance
“…In the literature, there is a case report regarding the migration of a bullet, which was retained in the body, as an embolism from the periphery to the center through the venous flow (4). Considering this related study in the literature, we have not seen any bullet migration as we observed in our case.…”
Section: Discussionsupporting
confidence: 66%
“…In the literature, there is a case report regarding the migration of a bullet, which was retained in the body, as an embolism from the periphery to the center through the venous flow (4). Considering this related study in the literature, we have not seen any bullet migration as we observed in our case.…”
Section: Discussionsupporting
confidence: 66%
“…Many authors reported cases of venous BE mostly managed by endovascular techniques [10][11][12][13] while others were managed by open surgery [14][15][16][17][18][19][20] or nonoperatively [5,21]. Open surgery was either used as a primary procedure or after failure of endovascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Low velocity bullet injury, as in civilian firearms, usually lodge within the body tissues, and rarely into the vascular tree. Vascular embolization of a bullet generally occurs when a small caliber, low velocity bullet breaches only one wall of a vessel, getting lodged within the vessel . The bullet generally follows the direction of blood flow (antegrade embolism).…”
Section: Discussionmentioning
confidence: 99%